Improved Message Diffusion Model for Node Coverage Problem of Ad Hoc Network Based on Node Visit Times - Zhe Yang; Lingzhi Li; Shukui Zhang; Yong Sun; Yanqin Zhu (International Journal of Distributed Sensor Networks)
It is of great significance to conduct researches on the message diffusion process for the node coverage problem, which can be generally abstracted as a random sampling model in the cooperative communication systems including the ad hoc and unstructured P2P networks. However, the message diffusion in the ad hoc network is not a completely independent random process. When forwarding the messages, the nodes will be influenced by such factors as degrees, visit times, and network connectivity. But the random sampling model does not take these factors into consideration, resulting in the overestimated node coverage degree. Discussing the message diffusion process of the cooperative communication systems like ad hoc network, this paper analyzes the causes of the inaccuracy problems of random sampling model and solves the problems by specially introducing the factors such as node degree and visit times. As for the E-R random network topology, it validates the effectiveness of the model proposed herein in contrast with the simulation experiment results. Compared with the random sampling model, the model proposed herein coincides better with the simulation results of the ad hoc network message diffusion process in the condition of network connectivity and its accuracy can meet the requirements for 3 and 5 visits.